Perbandingan Kekuatan Geser Braket Keramik Retensi dengan Perekatan Ulang dan Dua Teknik Pembersihan - Louise Cinthia Hutomo (DiscoverSys Inc., 2017)
Introduction: The purpose of this study is to measure the shear bond strength of rebonded mechanically retentive ceramic brackets prior which the base of the brackets was cleaned by two different methods. The first method was burnt out using spirituous lamp, the second method was burnt out using spirituous lamp and eventually sandblasted for 4 second. Methods: Thirty debonded ceramic brackets were prepared as the subject of this experiment. The shear bond strength was measured by Panke Pearson Equipment Limited, whereas the bond failure location of the rebonded brackets were examined using Zoom Stereo Microscope. T test was used to compare of the shear bond strength between two groups, whereas Chi Square analysis was used to determine the bond failure location of rebonded ceramic brackets. Results: Shear bond strength of rebonded ceramic brackets which were cleaned by second method was higher than those by first method, and had significant differences (p<0,01). Although the bond strength of rebonded ceramic brackets which were cleaned by first method was lower than the ones using second method, they were still above the clinical standard for intra oral retention. The bond failure location of rebonded ceramic brackets both by first method and second method after shear bond strength were tested, show no significant differences (p>0,05). The bond failure location of rebonded mechanically retentive ceramic brackets which cleaned by method I were mostly happen in the adhesive (86,7 %), and on the method n all the failure happens in the adhesive (100 %).